International experience in financing self-employed pensions - T. V. Zhukova (Финансы: теория и практика, 2022)
The rapid development of modern self-employment, the massive transition from employment to self-employment and vice versa is a challenge for traditional pension systems. The Organisation for Economic Co-operation and Development (OECD) responded by adopting compulsory state pension schemes for the self-employed shared with employees. Russia following global trends with a small-time lag, unlike others, provides an unconditional guarantee of social pensions. It is all the more important to study the advanced international experience in attracting the self-employed to pension insurance. This is the aim of the study. Research tasks are as follows: to identify different approaches to organizing pension insurance for the self-employed across OECD countries, to examine the mechanisms and factors arising, and to evaluate their performance. The research method is cluster analysis of the generated self-employed pensions parametric indicators database according to OECD data (2019–2021) (18 indicators as part of clustering, architecture, finance, performance factors) for 28 countries. The study identifies 3 clusters (approaches) to the organization of pension provision for the self-employed: 1 — employee-like mandatory contributions to state pension schemes; 2 — mandatory contributions with advantages; 3 — voluntary pension contributions with advantages. In general, none of the approaches can be called “the best”. The effectiveness of pension decreases with any form of low-income self-employed inclusion in income-based pension schemes, as well as dependent self-employment. The author concludes that for Russia alternative options for self-employed pensions are quasi-mandatory pension insurance, self-employed employee-like participation in voluntary funded pension schemes only, state co-financing, practical training in financial literacy without going into the depth of financial knowledge. Discussion for further research is a detailed study of the application of the results into self-employed pension insurance practice in Russia.